Fabrication of high-quality alumina coating through novel, dual-particle aerosol deposition. Issue 15 (15th October 2020) - Kim, Ik-Soo; Ko, Pil-Ju; Cho, Myung-Yeon; Lee, Yeon-Sook; Sohn, Hiesang; Park, Chulhwan; Shin, Weon Ho; Koo, Sang-Mo; Lee, Dong-Won; Oh, Jong-Min
Abstract: High-quality alumina (Al2 O3 ) coating has an extensive demand in the fields of optoelectronics, solar cells, and corrosion/impurity resistant coatings and cutting tools. The quality of alumina coating depends on its hardness and transparency. To obtain hard and highly transparent alumina coating, which is also a widely used ceramic material, a novel, aerosol deposition approach is presented in which the starting powder, used to fabricate Al2 O3 ceramic coatings, is composed of angular and spherical Al2 O3 particles. Films fabricated using angular:spherical Al2 O3 particle mixtures with ratios of 10:0, 7:3, 5:5, 3:7, and 0:10, showed significant variation in surface roughness and microstructure. The dramatic morphology modulation of the 3:7 angular:spherical Al2 O3 mixture film, resulting from the superposition hammering effect caused by the aerosol mixture, improved transmittance (84.7%) and hardness (13.6 GPa). Previous studies used high-energy approaches to optimize Al2 O3 film properties. This dual-particle approach, however, produces Al2 O3 film with excellent transmittance and hardness while achieving a fast coating speed (32 mm 2  × μm/min) without additional thermal treatment. Our proposed approach provides a novel and energy efficient method to produce transparent Al2 O3 films with superior durability.